Analysis Determination of Genetic Algorithm Crossover Point Problem in Travelling Salesman Problem - Nasution, Khairuddin; Haramaini, Tasliyah; Krianto Sulaiman, Oris; Zulfansyuri Siambaton, Mhd.; Hasibuan, Abdurrozzaq; Asaad, Mhd. (International Journal of Engineering and Technology, 2018)
Travelling Salesman Problem (TSP) is an optimization problem that can be applied to a variety of activities. Highlights of theTSPproblem is how the salesman can manage the journey so that the distance by which this is the optimum route is the best minimum distance. This study was formulated with the effect of determining the crossover point, especially probabilities of crossover in the search for the optimal route to theTSP. One goal of this research is to find the value of a good crossover probability in achieving optimal route. Crossover method used in this study is a partially mapped crossover (PMX). Selection is used Roulette wheel selection. From the tests carried out by using 20%, 40%, 60%, 80% and 99% can be found that a good crossover probability is 99%, with the determination of mutations worth of 0.05%. The number of generation is the generation 10000. Optimal route obtained from the data bays29.tsp is 10463.Â Â